2017
DOI: 10.1001/jamafacial.2017.0001
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Functional Nasal Reconstruction Using Structural Reinforcement

Abstract: IMPORTANCE Nasal reconstruction after Mohs surgery is a unique challenge in that it must satisfy both functional and aesthetic goals. Despite some advocacy in the literature for using structural reinforcement to achieve both functional and aesthetic outcomes in soft-tissue reconstruction, no study has validated this claim by comparing reconstruction with and without structural support. OBJECTIVE To evaluate the effectiveness of and need for structural reinforcement when reconstructing the nasal alar and sidewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
0
10
0
4
Order By: Relevance
“…22 Structural reinforcement with cartilage grafts of defects greater than 1.2 cm in diameter was found to have a decreased incidence of revision surgery due to retained competency of the nasal valve. 31…”
Section: Cartilage Graftingmentioning
confidence: 99%
“…22 Structural reinforcement with cartilage grafts of defects greater than 1.2 cm in diameter was found to have a decreased incidence of revision surgery due to retained competency of the nasal valve. 31…”
Section: Cartilage Graftingmentioning
confidence: 99%
“…32 In another study by Ezzat and Liu, the authors found that among patients with defects of the alar and sidewall subunits measuring over 1.2 cm, there was a statistically significant decreased rate of nasal obstruction in patients who had repair with cartilage grafting or suspension suture placement as compared with patients who had soft tissue-only reconstruction, further underscoring the importance of nasal valve collapse prevention in post-MMS nasal reconstruction. 33…”
Section: Strategies To Prevent Nasal Obstructionmentioning
confidence: 99%
“…1 Hospital de Clínicas Dr. Manuel Quintela, Montevidéu, Uruguai. 2 Facultad de Medicina de la Universidad de la República, Montevidéu, Uruguai.…”
Section: ■ Resumounclassified
“…Existem inserções fibrosas das cartilagens alar e laterais em direção à abertura piriforme, bem como a espessura e consistência da pele supra-adjacente, que são fundamentais para o funcionamento da válvula nasal. Portanto, a contribuição do suporte na reconstrução da asa nasal é independente da quantidade de cartilagem ressecada, e os defeitos basais ou marginais, sem ressecção da cartilagem, também vão precisar de algum tipo de suporte 2 .…”
Section: Introductionunclassified